Comprehensive Study of Patient-Centered Care in Transforming Healthcare through Personalized Treatment Plans and Balancing Innovation with Patient Rights - Alanazi, Mohammed Hryuith; Alanzei, Rehab Abdullah; Althayrayan, Abdullah Mohsen M; Almalki, Rashid Musad Shraz; Alyami, Dhafer Ali Saleh; Alharbi, Sultan Ali Muflih; Alanzei, Malak Khalaf Alnori; Alshuhayli, Bayan Fawzi Nasser; Al Gareh, Hussein Mohsen Abdulrahman; Almaulhim, Shmah Mansoor; Althaiban, Salman Saleh (Journal of Ecohumanism, 2024)
This paper scrutinizes how PCC is central to redefining twenty-first-century healthcare delivery, the embrace of individualized treatment approaches, and concerns over innovativeness and patients’ rights. The developments in information technology and communications, including artificial intelligence and analytical genomics, as well as in machine learning, mean that focus has been placed on precision medicine that meets the needs of individual consumers. However, this innovation is also significantly tied to the ethos of patients’ rights, autonomy, and informed consent. This paper aims to provide a systematic literature review on the current state of patient-centered care, a description of the method of analyzing patient-centered care, and a reflection on improving healthcare delivery while respecting the patient's dignity. Survey responses from patients, findings obtained from clinical case reports, and measurements of healthcare organizational measures are employed to establish the benefits and drawbacks of patient-centered strategies.